PENGARUH BERBAGAI ENKAPSULAN DALAM PROSES ENKAPSULASI ASAM SITRAT SEBAGAIACIDIFIER DALAM PAKAN AYAM PEDAGING TERHADAP KECERNAAN PROTEIN DAN ENERGI MET ABOLIS - M. Halim Natsir (Faculty of Animal Science, Universitas Brawijaya, 2009)
The aim of this research was to examine the influence of several encapsulants in encapsulating citric acid used as acidifier on protein digestibility and metabolizable energy in broilers. The materials used in this research were 20 broilers of 21 days of age, liquid citric acid and encapsulated citric acids. The encapsulants used were maltodextrin, lactoglobulin and zeolite. Broilers were randomly allotted to five dietary treatments with 4 replication each. The variables observed were crude protein digestibility (DCPmanure and DCP/aecaiJ. apparent metabolizable energy (AME) and apparent metabolizable energy corrected N (AMEn). Data were analyzed by using Completely Randomized Design. The difference among the treatments was further tested by using Duncan Multiple Range Test. The result of this research showed that while citric acid encapsulated with maltodextrine gave significantly different effect (P<0.05) and the highest crude protein digestibility (DCPmanurd. citric acid encapsulated with either lactoglobulin and and maltodextrine gave significantly highest results on digestibility (DCP1aecaiJ (P<0.05) and AME and AMEn (P<0,01). It can be concluded that maltodextrin was the best choice of encapsulant for citric acid based on the highest protein digestibility and metabolizable energy (JIIPB 2009 Vol 19 No 1: 1-9). Key words : Citric Acid, Encapsulation, Protein Digestibility, Metabolizable Energy, Broiler